2022
DOI: 10.1016/j.celrep.2021.110220
|View full text |Cite
|
Sign up to set email alerts
|

2-Hydroxyglutarate destabilizes chromatin regulatory landscape and lineage fidelity to promote cellular heterogeneity

Abstract: Highlights d Inhibition of aKG-dependent demethylation destabilizes chromatin regulatory landscape d 2HG subverts lineage fidelity and increases cell-level variability in motif accessibility d 2HG-high breast tumors display enhanced cellular heterogeneity d A2P eradicates heterogeneity in high 2HG-producing basallike cancer cells

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 92 publications
0
4
0
Order By: Relevance
“…Other cluster 8 and 10 metabolites are predicted to be synthesized by the nematode but not the bacterium. These include the sphingolipid metabolite phosphorylethanolamine ( 45 ) and 2-hydroxyglutaric acid, a butanoate pathway-derived metabolite that, in mammalian cells, serves as an oncometabolite that influences DNA repair and chromatin structure ( 46 ). Among the cluster 8 and 10 metabolites predicted to be specific to bacterial physiology is the polyamine acetyl-putrescine (cluster 8).…”
Section: Resultsmentioning
confidence: 99%
“…Other cluster 8 and 10 metabolites are predicted to be synthesized by the nematode but not the bacterium. These include the sphingolipid metabolite phosphorylethanolamine ( 45 ) and 2-hydroxyglutaric acid, a butanoate pathway-derived metabolite that, in mammalian cells, serves as an oncometabolite that influences DNA repair and chromatin structure ( 46 ). Among the cluster 8 and 10 metabolites predicted to be specific to bacterial physiology is the polyamine acetyl-putrescine (cluster 8).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, under conditions that typically promote erythroid differentiation, the expression of IDH2R140Q in TF-1 cells increased DNA methylation and H3K9me3 at the promoter of a key differentiation gene, HBG , suppressed HBG expression and blocked differentiation, all of which were reversed upon inhibition of mutant-IDH [ 40 ]. Aberrant DNA and histone methylation have also been reported in mutant-IDH expressing haematopoietic stem and progenitor cells in vivo [ 23 , 39 ] and in numerous studies where 2-HG is supplemented or mutant-IDH expressed in non-haematological malignancies [ 22 , 31 , 35 , 45 , 47–51 ]. Moreover, analyses of AML patient samples have shown that DNA hypermethylation in TET2-mutant AMLs overlaps with the hypermethylation phenotype of IDH-mutant AML [ 44 , 52 , 53 ].…”
Section: Biology Of Idh Mutations In Amlmentioning
confidence: 99%
“…Beyond the impact of those changes on the cell's metabolism, epigenome regulators are also highly sensitive to changes in intracellular metabolism. Indeed, a cancer cell's epigenetic and transcriptional landscape can be altered, for example, by iron endocytosis (54), proline metabolism (55), or the metabolite 2-hydroxyglutarate (56).…”
Section: Cellular Plasticity As a Driver Of Cancer Progressionmentioning
confidence: 99%